Common genetic variants at the 11q13.3 renal cancer susceptibility locus influence binding of HIF to an enhancer of cyclin D1 expression. - Schödel, J; Bardella, C; Sciesielski, L; Brown, J; Pugh, C; Buckle, V; Tomlinson, I; Ratcliffe, P; Mole, DR (2012)
Although genome-wide association studies (GWAS) have identified the existence of numerous population-based cancer susceptibility loci, mechanistic insights remain limited, particularly for intergenic polymorphisms. Here, we show that polymorphism at a remote intergenic region on chromosome 11q13.3, recently identified as a susceptibility locus for renal cell carcinoma, modulates the binding and function of hypoxia-inducible factor (HIF) at a previously unrecognized transcriptional enhancer of CCND1 (encoding cyclin D1) that is specific for renal cancers characterized by inactivation of the von Hippel-Lindau tumor suppressor (pVHL). The protective haplotype impairs binding of HIF-2, resulting in an allelic imbalance in cyclin D1 expression, thus affecting a link between hypoxia pathways and cell cycle control.